2010
DOI: 10.1016/j.humpath.2010.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Higher levels of GATA3 predict better survival in women with breast cancer

Abstract: The GATA family members are zinc finger transcription factors involved in cell differentiation and proliferation. GATA3 in particular is necessary for mammary gland maturation, and its loss has been implicated in breast cancer development. Our goal was to validate the ability of GATA3 expression to predict survival in breast cancer patients. Protein expression of GATA3 was analyzed on a high density tissue microarray consisting of 242 cases of breast cancer. We associated GATA3 expression with patient outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
128
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(150 citation statements)
references
References 44 publications
14
128
1
3
Order By: Relevance
“…[8][9][10] A metaanalysis has also indicated that GATA3 is integrally involved in the ERα pathway 24 whose activation is presumably critical for breast tumorigenesis and tumor progression. Recent evidence indicates the involvement of steroid hormone receptor signals, especially ER and androgen receptor (AR) pathways, in bladder cancer growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] A metaanalysis has also indicated that GATA3 is integrally involved in the ERα pathway 24 whose activation is presumably critical for breast tumorigenesis and tumor progression. Recent evidence indicates the involvement of steroid hormone receptor signals, especially ER and androgen receptor (AR) pathways, in bladder cancer growth.…”
Section: Discussionmentioning
confidence: 99%
“…5,7 A number of immunohistochemical studies in breast cancer tissue specimens have demonstrated that lower expression levels of GATA3 correlate with higher tumor grade and precisely predict poorer patient outcomes. [8][9][10] Thus, GATA3 is believed to be a breast tumor suppressor.…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 and GATA3 corepress basal-like breast cancer genes D Tkocz et al GATA3 has been known for some time to be a good prognosis indicator in breast cancers with higher GATA3 levels predicting for better prognosis in ERa-positive breast cancers (Yoon et al, 2010). GATA3 has been shown to inhibit breast cancer metastasis through the reversal of epithelial-mesenchymal transition (Yan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Gata-3 deficiency results in an expansion of luminal progenitors and a concomitant block in differentiation whilst introduction of Gata-3 into a stem cell-enriched population induced maturation along the alveolar luminal lineage (Asselin-Labat et al, 2007). In breast cancers, GATA3 is thought to be a marker of good prognosis with highest expression levels in luminal A breast cancers (Jacquemier et al, 2009;Yoon et al, 2010). Loss of GATA3 function is associated with increased tumorigenesis and was found to be enriched in non-BRCA1/BRCA2 familial breast cancers (Arnold et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…GATA3 is expressed at higher levels in luminal versus basal A and B subtypes of BC consistent with its luminal localization. A correlation was found between higher levels of GATA3 and better survival in BC patients (135,136). miR-29b promotes luminal differentiation and targets a network of angiogenic and prometastatic regulators such as vascular endothelial growth factor isoform A (VEGFA), angiopoietin-like 4 (ANGPTL4), platelet-derived growth factor (PDGF), lysyl-oxidase (LOX), MMP-9, TGFβ and integrin subunits α6 and β1 (132), which modify the tumor microenvironment.…”
Section: Breast Cancer Metastasis Suppressing Mirsmentioning
confidence: 99%